Trends in Al-Qur’an Learning Applications for Indonesian Students: Solutions for Learning Qur’an during the Covid-19 Pandemic? - i'anatut Thoifah (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
Government policy related to the Covid-19 pandemic conditions requires learning at school and learning the al-Qur’an at TPQ online, so must innovate and adapt to awareness and intelligence disclosure, one of which is the number of applications for learning the al-Qur’an as an alternative in this condition. This study aims to identify trends, determine the distribution and analyze the appropriateness of the al-Qur'an learning application using descriptive qualitative research, with 988 students as respondents from 38 junior high schools and high schools in Indonesia. This research shows that there are 10 application trends based on the highest number of users, including the al-Quran Indonesia, muslim pro, al-Quran, umma, my Quran dan terjemah, al-Quran digital, youtube, al-Quran terjemah, al-Quran bahasa Indonesa, belajar membaca al-Quran. The overall application level is 81% based on the TAM (Technology Acceptance Model) theory, which is determined by the benefits of use, interest and completeness of features, besides the trend of these 10 applications in knowledge or cognition can be a companion solution for learning the al-Qur'an during the covid-19 pandemic